Sediment Porosity Investigation of Tidal Zone in Teluk Penyu Cilacap, Indonesia - Florencius Eko Dwi Haryono; Hydian Suripto; Mukti Trenggono (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
The sediment fraction is the grain size, sorting and composition of the sediment, while sediment porosity is the ratio of the volume of the cavity in total volume. The cavity in marine sediment is a habitat of decomposing organisms. The research aimed to analyze the relationship between the fraction and porosity of tidal zone sediments in coastal of Teluk Penyu Cilacap. This survey method used sediment core samplers, sediments fractions used sieve method and the porosity used method of Reeve (1986), and analysis used software SPSS20. The results showed that tidal zone sediments in coastal of Teluk Penyu Cilacap were dominated by the fine sand with percentage when high water was higher than low water. Based on mean size diameter, sediment near Serayu river was found medium sand and far was fine sand. Based on linear regression, the relation between sediment fraction and porosity at high water and low water was obtained very weak, but when low water was found in opposite condition to the high water, that the greater of sediment diameter was smaller of porosity. High porosity indicates a wider space between the sediments and allows more decomposing organisms. It is important to consider the results of the clearing of organic matter which affects to fish resources in coastal waters. Keywords: sediment fractions, porosity, teluk penyu